2018
DOI: 10.21010/ajid.v12i1s.11
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Risk Factor of Toxoplasmosis in Schizophrenia Patients Referred to Grhasia Psychiatric Hospital, Yogyakarta, Indonesia

Abstract: Background: Toxoplasmosis is an infectious disease caused by protozoan parasite called Toxoplasma gondii. Toxoplasma gondii is an intracellular protozoan parasite belong to phylum Apicomplexa, is an obligate parasite in mammals. The active proliferating trophozoites or tachyzoites are usually seen in the acute stage of infection, while the resting bradyzoites formed tissue cysts are primary found in muscle and brain. Human infection occurs mainly by ingesting food or water contaminated with oocyst or eating an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…gondii antibodies in both serum and cerebrospinal fluid in patients with recent-onset schizophrenia [ 14 , 15 ]. More recently, a study of 81,912 individuals from the Danish Blood Donor Study also found evidence that T. gondii and schizophrenia were statistically associated [ 177 ] while Muflikhah et al also showed that seropositivity was higher at 69% for the group of patients with schizophrenia compared to the control group at 66%; however, the latter was not considered statistically significant [ 178 ]. In addition, Alipour et al and Kezai et al showed a significant difference of the seropositivity rate between controls and patients with schizophrenia: specifically, 67.7% in patients with schizophrenia vs. 37.1% in control patients and 70% in patients with schizophrenia vs 52.9% in controls [ 179 , 180 ].…”
Section: Methodology and Resultsmentioning
confidence: 99%
“…gondii antibodies in both serum and cerebrospinal fluid in patients with recent-onset schizophrenia [ 14 , 15 ]. More recently, a study of 81,912 individuals from the Danish Blood Donor Study also found evidence that T. gondii and schizophrenia were statistically associated [ 177 ] while Muflikhah et al also showed that seropositivity was higher at 69% for the group of patients with schizophrenia compared to the control group at 66%; however, the latter was not considered statistically significant [ 178 ]. In addition, Alipour et al and Kezai et al showed a significant difference of the seropositivity rate between controls and patients with schizophrenia: specifically, 67.7% in patients with schizophrenia vs. 37.1% in control patients and 70% in patients with schizophrenia vs 52.9% in controls [ 179 , 180 ].…”
Section: Methodology and Resultsmentioning
confidence: 99%
“…Toxoplasma infection of the brain undoubtedly affects neuro-inflammatory processes, including microglial activation, the levels of inflammatory cytokines, and the number of peripheral immune cells occurring during the infection. All these biochemical and cellular processes alter behavior in various ways and might affect the risk of schizophrenia and the course of the disease [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated antibody levels have also been linked to schizophrenia as compared with other patient groups [ 23 , 24 ]. The results of our study did not show a statistically significant correlation with antibody levels.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of T. gondii in the human population in Indonesia, one of the countries most intensely affected by this parasite, is estimated to be around 50% [7]. The seroprevalence of toxoplasmosis was reported to be 62.5% (394/630) and 67.7% (107/158) in Central Java and Yogyakarta, respectively [7,8]. In North Sulawesi, a high prevalence (58.5%; 501/856) was also reported in humans, but the rate was only 2.3% in pigs [7].…”
Section: Introductionmentioning
confidence: 99%